Influence of Maternal Demographic and Obstetric Characteristics on Neonatal Birth Weight - Noura Elawam; Sabria Salam (AlQalam Journal of Medical and Applied Sciences, 2023)
Aims. The purpose of current study was to estimate the prevalence of low birth weight among Libyan newborns, as well to evaluate the impact of maternal personal and obstetric characteristics on birth weight. Methods. A cross section study was conducted among 300 women with a singleton; intrauterine pregnancy delivered at Al-Jala Hospital Tripoli, Libya in period of Jun, 1st till December,31st 2022 Measure of Socio-demographic characteristic; birth outcome and obstetric risk information were obtained from patients’ face to face interview before discharge from the postnatal word. Results. The birth mean weight of our sample was 3.117±0.65 Kg; about 16.2% had low birth weight (LBW). Prematurity has a significant influence on BW where mothers who had history of premature baby more liable to deliver baby with LBW (56%) compared with mothers who had no previous history of prematurity (12.5%). Mothers with positive history of LBW babies had higher risk to deliver LBW babies with a percentage of 46.2% vs. 11.7% respectively (p=0.0001). Mothers complicated with abruptioplacenta more likely to deliver LBW babies (25.9%) than mothers without (15.3%). Conclusions. The major determinants of low birth weight were prior history of low birth weight or history of prematurity, and pregnancy complicated with diabetes mellitus. Future research should focus on factors of potential data are either unavailable or inconclusive